A Photoactivatable Small‐Molecule Probe for the In Vivo Capture of Polyketide Intermediates. Issue 72 (28th November 2019) - Kilgour, Samantha L.; Jenkins, Robert; Tosin, Manuela
Abstract: A photolabile carba(dethia) malonyl N ‐acetylcysteamine derivative was devised and prepared for the trapping of biosynthetic polyketide intermediates following light activation. From the lasalocid A polyketide assembly in a mutant strain of the soil bacterium Streptomyces lasaliensis, a previously undetected cyclised intermediate was identified and characterised, providing a new outlook on the timing of substrate processing. Abstract : Biocatalysis : A 4, 5‐dimethoxy‐2‐nitrobenzyl (DMNB)‐protected probe was devised and utilised for the capture of polyketide‐derived species in bacterial fermentative cultures (see figure).